The Hadith "No Loan Coupled with a Sale is Permissible" and its applications in the field of leasing in Islamic banks - Abdelrehim, Gamal Mohamed Ali; Mohammad Zaini Yahaya,; Nik Abdul Rahim Nik Abdul Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to elucidate the concept and reasoning behind the prohibition of combining a loan and a sale in Islamic jurisprudence. The research employs descriptive, analytical, and comparative methodologies to explore the various manifestations of such combinations from the perspective of Islamic legal scholars. The hadith that forbids this combination is substantiated by distinguished narrators, and its implications have been extensively analyzed. The legal scholars' differing rulings hinge on the presence of stipulations within the transaction. Two primary viewpoints have been identified: the Shafi'i perspective and the majority consensus. The majority consensus postulates that the rationale behind the prohibition stems from a mixture of ignorance and potential usury, while the Shafi'i viewpoint suggests that it results from a lack of clarity regarding the price. If the two contracts - loan and sale - are fused with a stipulation, all legal scholars agree that this combination is forbidden, in order to prevent the aforementioned reasons from becoming a reality. Conversely, if the combination occurs without a stipulation, the Shafi'i perspective deems it permissible, even if the price of the sale or lease is higher than the fair market value. The majority opinion, on the other hand, limits its acceptability to transactions reflecting fair market value, in order to prevent the loan from serving as a conduit for usury. In conclusion, this study provides clarity on the different forms and reasoning behind the rulings related to combining a loan and a sale in Islamic jurisprudence. This research is particularly valuable for those working within the Islamic financial system who seek to ensure Sharia compliance. By comprehending the prohibition of combining a loan and a sale, they can avoid engaging in practices that are impermissible in Islam.